Age at Onset of DSM-IV Pathological Gambling in a Non-Treatment Sample: Early- versus Later-Onset - Black, Donald W. (Compr Psychiatry, 2015)
BACKGROUND: Pathological gambling (PG) is a prevalent and impairing public health problem. In this study we assessed age at onset in men and women with PG and compared the demographic and clinical picture of early- vs. later-onset individuals. We also compared age at onset in PG subjects and their first-degree relatives with PG. METHOD: Subjects with DSM-IV PG were recruited during the conduct of two non-treatment clinical studies. Subjects were evaluated with structured interviews and validated questionnaires. Early-onset was defined as PG starting prior to age 33 years. RESULTS: Age at onset of PG in the 255 subjects ranged from 8 to 80 years with a mean (SD) of 34.0 (15.3) years. Men had an earlier onset than women. 84% of all subjects with PG had developed the disorder by age 50 years. Early-onset subjects were more likely to be male, to prefer action games, and to have substance use disorders, antisocial personality disorder, attention deficit/hyperactivity disorder, trait impulsiveness, and social anxiety disorder. Later-onset was more common in women and was associated with a preference for slots and a history of sexual abuse. CONCLUSIONS: Age at onset of PG is bimodal and differs for men and women. Early- and later-onset PG have important demographic and clinical differences. The implications of the findings are discussed.